Analyzing flexural strength data of ice: how useful is explainable machine learning? - Buil, Patrik; Kellner, Leon; Ehlers, Sören; von Bock und Polach, Rüdiger Ulrich Franz (American Society of Mechanical Engineers, 2022)
The climate crisis results in a rapid sea ice decline, making shipping routes accessible for longer durations throughout the year and therefore increasing maritime traffic. At the same time, ice-structure interaction is known to cause damage to ships and structures. In this context, the flexural strength is a key property of the ice. It is also an important factor in the process of the formation of ice ridges which then act as obstacles to marine transit.